Предмет: Алгебра,
автор: LLIKOJIbHИK
Здравствуйте! Помогите решить уравнение (х-3)(х+2)-(х-1)(х+1)=3х+7
Ответы
Автор ответа:
0
+2-3х-6--1-3х-7=0 ( и - взаимно уничтожается)
-6х-12=0
6х=-12
х=-2
-6х-12=0
6х=-12
х=-2
Автор ответа:
0
степень
Автор ответа:
0
x^2+2x-3x-6-(x^2+x-x-1)=3x+7
x^2+2x-3x-6-x^2+1=3x+7
-x-5=3x+7
-4x=12
x=-3
x^2+2x-3x-6-x^2+1=3x+7
-x-5=3x+7
-4x=12
x=-3
Автор ответа:
0
ЛОЛ
Автор ответа:
0
;D
Похожие вопросы
Предмет: Қазақ тiлi,
автор: botagzkenzalieva
Предмет: Русский язык,
автор: crazygirlbaby
Предмет: Физика,
автор: FMMFM
Предмет: Математика,
автор: Аноним